Tari Boria Etnomatematika pada Tari Boria di Pulau Penyengat: Etnomatematika pada Tari Boria di Pulau Penyengat - Scesa, Laidy Aprilia; Febrian , Febrian; Rahmatina, Desi; Febrian, Febrian (Jurnal Gantang, 2023)
Boria dance is an art from Penyengat Island that shows the skill of marching and dancing to the rhythm of music in various song rhythms. The dance is performed by paying attention to the floor pattern, appropriateness of Movement, and appropriate rhythm. All of this is done to achieve the beauty of the dance. This research examines the ethnomathematics of the Boria dance on Penyengat Island. This research is qualitative research with an ethnographic approach. The data source for this research is arts activists at the Penyengat Heritage Cultural Studio. Data was collected by observation, interviews, and documentation with the main instrument, the researcher himself. Next, data analysis was carried out using domain, taxonomy, component, and cultural theme analysis. The research results found that there were mathematical activities, namely counting the beats made by dancers, measuring the distance between dancers before and after entering the stage, and designing the movements and floor patterns of the Boria Dance. The mathematical concepts in this research are multiplication, non-standard units of measurement, angles, and flat figures.